Kinerja Dinas Perhubungan Kabupaten Tabanan Dalam Menekan Angka Kecelakaan Melalui Program Trans Serasi (Sejahtera Aman Berprestasi) - Ayu Kadek Septian Pradnyadari; Putu Eka Purnamaningsih; Ni Wayan Supriliyani (Ethics and Law Journal: Business and Notary, 2024)
The purpose of this research is to find out how the performance of Tabanan Regency Transportation Agency in reducing the number of accidents through the Trans Serasi (Sejahtera Aman Berprestasi) program. Through a qualitative approach with a case study method, data was obtained through interviews with various related parties, including students, parents, and related parties in the Transportation Agency. The results of the analysis show that the performance of Dinas Perhubungan Tabanan District faces several challenges and supporting factors. The Trans Serasi program, initially free of charge, has helped reduce the number of accidents among junior high school students. However, the paid and limited program in some sub-districts resulted in unrest and an increase in accidents. Supporting factors for performance include the availability of facilities and infrastructure, monitoring and evaluation, human resources, safety assurance, and timeliness. However, the lack of a fleet and information disclosure regarding the change of the program to a paid one are inhibiting factors. Nevertheless, the Transportation Agency is trying to improve performance by planning to expand the program to all sub-districts and increasing information transparency. This study provides an overview of the complexity of implementing a school transport program and emphasizes the importance of involving all relevant parties in ensuring the sustainability and effectiveness and efficiency of the program. Keywords: Transportation Agency, Trans Serasi Program, Accident Rate, Qualitative Abstrak Tujuan dari riset ini ialah guna mengetahui Bagaimana kinerja Dinas Perhubungan Kabupaten Tabanan Dalam Menekan Angka Kecelakaan Melalui Program Trans Serasi (Sejahtera Aman Berprestasi). Melalui pendekatan kualitatif dengan metode studi kasus, data diperoleh melalui wawancara dengan berbagai pihak terkait, termasuk siswa/I, orang tua, dan pihak terkait di Dinas Perhubungan. Hasil analisis menunjukkan bahwa kinerja Dinas Perhubungan Kabupaten Tabanan menghadapi beberapa tantangan dan faktor pendukung. Program Trans Serasi, awalnya gratis, telah membantu menurunkan angka kecelakaan di kalangan siswa/I SMP. Namun, program berbayar dan terbatas di beberapa kecamatan mengakibatkan keresahan dan peningkatan kecelakaan. Faktor pendukung kinerja meliputi ketersediaan sarana dan prasarana, monitoring dan evaluasi, sumber daya manusia, jaminan keselamatan, dan ketepatan waktu. Namun, kurangnya armada dan keterbukaan informasi mengenai perubahan program menjadi berbayar menjadi faktor penghambat. Meskipun demikian, Dinas Perhubungan berupaya memperbaiki kinerja dengan merencanakan perluasan program ke seluruh kecamatan dan meningkatkan transparansi informasi. Penelitian ini memberikan gambaran tentang kompleksitas implementasi program transportasi sekolah dan menekankan pentingnya keterlibatan semua pihak terkait dalam memastikan keberlanjutan serta efektivitas dan efisiensi program tersebut.